Innovative Manufacturing of Fish-Enriched Instant Noodles: A Perspective of Circular Economy and Sustainability Approach - Irem Kılınç; Riya Liuhartana Nasyiruddin; Adityas Agung Ramandani; Berna Kılınç (CV. Media Inti Teknologi, 2025)
Background of Study: Innovative food solutions are essential for low- and middle-income countries facing food insecurity, malnutrition, and environmental degradation. The high consumption of instant noodles in Indonesia, especially among low-income and nutritionally vulnerable populations, presents a strategic opportunity to enhance nutritional quality by utilizing underutilized fish resources and seafood by-products. Aims and Scope of Paper: This study aims to evaluate the development potential of fish-enriched instant noodles within the framework of circular economy and sustainability. It covers the nutritional enhancement, food waste reduction, and environmental impacts of such innovations, particularly focusing on the feasibility of industrial-scale implementation in the Indonesian context. Methods: A multidisciplinary approach was employed, combining nutritional science, food technology, and sustainability principles. The production process involved the selection of fish-based ingredients and by-products, dough formulation, processing through steaming and energy-efficient drying, and the use of biodegradable packaging. The innovation was assessed in terms of nutritional improvement, environmental impact, and industrial scalability. Result: The results demonstrated that fish-enriched instant noodles significantly improve protein content, omega-3 fatty acids, calcium, and micronutrients compared to conventional instant noodles. Moreover, the adoption of renewable energy, water recycling systems, and eco-friendly packaging effectively reduced the carbon footprint and waste associated with production. This innovation aligns with several United Nations Sustainable Development Goals (SDGs), including Goal 2 (Zero Hunger), Goal 3 (Good Health and Well-being), Goal 12 (Responsible Consumption and Production), and Goal 14 (Life Below Water). Conclusion: The development of fish-enriched instant noodles offers a functional food solution that not only enhances community nutrition but also reduces food waste and supports sustainable food systems. Despite its promising potential, challenges remain, including limited regulatory frameworks, technological readiness, and low consumer awareness of the benefits of circular economy-based foods. Cross-sector collaboration is essential to achieve broader implementation of this innovation on an industrial scale.